Análise temporal de atríbutos físicos do solo em áreas cultivadas em plantio direto com e sem terraços agrícolas - Jung, Amanda Taissa (My University, 2024)
Terracing within no-tillage systems can modulate the soil water balance and structural evolution on cultivated hillslopes. Over four crop seasons (2019–2022), we evaluated the effect of terraces on physical–hydraulic attributes of a medium-textured Red-Yellow Oxisol in Ponta Grossa, Paraná State, Brazil, by comparing no-tillage with terraces (CT) and without terraces (ST) in two 1.54-ha megaplots. Soil was sampled at 0–0.10 and 0.10–0.20 m to determine bulk density (Ds), total porosity (Pt), macro- and microporosity, penetration resistance (RP), field capacity (FC), permanent wilting point (PWP), and available water capacity (AWC); saturated hydraulic conductivity (Ksat) and basic infiltration rate (VIB) were measured at 0–0.05 m. A regular 20-m grid yielded 144 samples analyzed per year. Treatment comparisons used meancomparison tests (Test T), with within-year analyses and interannual (paired) contrasts. Terracing increased soil water storage in the profile, with higher FC, PWP, and AWC under CT—particularly at 0.10–0.20 m—relative to ST. Subsurface compaction persisted in both systems, with RP > 2.0 MPa at 0.10–0.20 m in every year and higher means in 2022 under CT (2.81 MPa) than ST (2.37 MPa), while surface RP generally remained below the restrictive threshold. Macroporosity declined over time (coincident with increases in Ds and RP), with treatment differences varying by layer and year. Regarding transmission properties, Ksat and VIB decreased over time in both CT and ST; Ksat showed no consistent treatment effect, whereas VIB was, on average, lower under CT and showed greater interannual variability in ST. Collectively, the findings indicate a partial decoupling between retention and transmission under no-tillage: terraces enhanced water retention/storage (FC, PWP, AWC) but did not produce a systematic improvement in pore connectivity governing flow (Ksat, VIB) within the study window. We conclude that, in this setting, terracing acted as hydrological mitigation— raising water content and stability in the profile—without removing the subsurface compaction typical of long-term no-tillage; therefore, the initial hypothesis was partially supported.
Keywords: sistema plantio direto; terraceamento agrícola; Latossolo; densidade do solo; resistência à penetração; condutividade hidráulica saturada; infiltração; água disponível; no-tillage system; agricultural terracing; Oxisol; bulk density; penetration resistance; saturated hydraulic conductivity; infiltration; available water